Modelagem e avaliação do efeito da soldagem a arco sobre a qualidade da energia elétrica em plantas industriais - Silva, Ezio Fernandes da (2013)
Currently there is great concern about the various aspects related to power quality (PQ), as these factors may somehow cause damage to sensitive equipment and other anomalies that represent losses to consumers in general. Given this representation, the regulatory agencies of the electricity sector have been concerned to establish standards, procedures, rules and recommendations to avoid poor quality of the electric power generated, mainly due to the fact that industries have nature loads intrinsically disturbing, as resulting from the welding operations. But a trade of great prominence in the economy is the metallurgical industries, which mostly use welding machine in its production process. Within this context fit the present proposal for doctoral thesis, which is focused on the development of simulation tool to study the behavior of an industrial unit with welding power sources in operation, analyzing the effects caused by this type of load, of intermittent and random character, to the network. For this, a model has been developed to simulate the electric arc welding to the process MIG/MAG and subsequently to join this model with the topology of a welding machine. Through the model of a welding machine developed in a Simulink platform, the behavior of the instantaneous currents and voltages at the entrance of the welding machine at the point of common coupling (PCC) and in electric arc welding became possible, providing conditions for these data were sufficient to qualify and quantify the effects of the MIG/MAG welding process over the PQ. Indicators of PQ have been analyzed, namely, instantaneous flicker sensation (Sf), severity index flicker (Pst) and interharmonics frequencies. Within this scenario the proposal of this thesis, which aims to conduct a simulation program for various welding machines MIG/MAG process for determining in advance the disturbances caused to the electric power network, contributing to the analysis of new projects and/or already installed.